Protein pattern and plasmid profile of lactic acid bacteria isolated from dahi, a traditional fermented milk product of Pakistan - Soomro, Aijaz Hussain (Array, 2007)
A total of 116 isolates were identified from randomly collected market dahi samples from Rawalpindi, Pakistan. Lactic acid bacteria dominated the microbial population of dahi and were identified according to their morphological and physiological characteristics. Among these lactobacilli were frequently occurring organisms. The phenotypic and biochemical analyses gave a diversity of species (8 presumptive species). The most abundant species were Lactobacillus delbrueckii subsp. bulgaricus (28 isolates) and Streptococcus thermophilus (25 isolates). Some contaminants such as Staphylococcus, Micrococcus and Saccharomyces spp. were also observed. The whole cell protein profiles of selected strains of lactic acid bacteria were examined by SDS-PAGE. It was observed that each species yielded a different electrophoretic pattern. It was further observed that among the strains investigated for the analysis of plasmid DNA 22 strains were found positive, 8 strains of L. delbrueckii subsp. bulgaricus followed by 5 of L. acidophilus, 4 of L. casei, 3 of L. helveticus and one of each L. delbrueckii subsp. delbrueckii and L. delbrueckii subsp. lactis, whereas no plasmid was observed in S. thermophilus and L. lactis strains investigated during the study. All the plasmids isolated were mostly large size plasmids and ranged from 20 to 25 kb in size